Stresor Pubertas dan Keterlibatan Orang Tua pada Remaja [Pubertal Stressors and Parental Involvement in Adolescents] - Ganda Sari (Diligentia: Journal of Theology and Christian Education, 2023)
The science of developmental psychology has explained the challenges of adolescence, including the causes of adolescent changes, developmental tasks and things that can cause stress in adolescents. These challenges are stressors for adolescents and if not resolved properly, can increase prolonged stress and ultimately adolescents are unable to complete their developmental tasks properly. Parents, as God's representatives, can play a role through emotional and physical involvement that aims to reduce stressors. For this reason, the purpose of this paper is to provide insight to parents about things that happen in adolescent development, stressors faced by adolescents and proposed parental attitudes towards adolescents. Based on the results of the literature review, it is found that parents who are emotionally and physically involved show that the parents understand and understand the needs of adolescents. Forms of parental involvement in adolescents' needs through emotional support, appreciation support, instrumental support and informative support. BAHASA INDONESIA ABSTRACT: Ilmu psikologi perkembangan telah menjelaskan tantangan-tantangan pada masa remaja, termasuk penyebab perubahan remaja, tugas-tugas perkembangan dan hal-hal yang dapat menyebabkan stres pada remaja. Tantangan-tantangan tersebut merupakan stressor bagi remaja dan jika tidak diselesaikan dengan baik, dapat meningkatkan stres yang berkepanjangan dan pada akhirnya remaja tidak dapat menyelesaikan tugas-tugas perkembangannya dengan baik. Orang tua sebagai wakil Tuhan dapat berperan melalui keterlibatan emosional dan fisik yang bertujuan untuk mengurangi stresor. Untuk itu, tujuan dari penulisan ini adalah untuk memberikan pemahaman kepada orang tua mengenai hal-hal yang terjadi pada perkembangan remaja, stressor yang dihadapi remaja dan usulan sikap orang tua terhadap remaja. Berdasarkan hasil tinjauan pustaka, ditemukan bahwa orang tua yang terlibat secara emosional dan fisik menunjukkan bahwa orang tua mengerti dan memahami kebutuhan remaja. Bentuk keterlibatan orang tua terhadap kebutuhan remaja melalui: dukungan emosional, dukungan penghargaan, dukungan instrumental dan dukungan informatif.